Rice yellow mottle virus Infection and Reproductive Losses in Rice (Oryza sativa Linn.) - Onwughalu, J.T.; Abo, M.E.; Okoro, J.K.; Onasanya, A.; Sere, Y. (Science Alert, 2011)
The study on Rice yellow mottle virus (RYMV) infection and reproductive losses in rice was carried out under screenhouse condition in Nigeria. Thirty-five rice varieties were evaluated for RYMV resistance. Percent productive tillers, date to 50% flowering and percent spikelets fertility per plant were between 43.2-96.7%, 57.67-112 days and 0-71.8%, respectively. Number of panicles per plant, number of grains per panicle and 1000 grain weight per plant were between 8.33-45.67, 0-77 and 0-27.57 g, respectively. Yield losses of between 17-100% were obtained from all the rice varieties evaluated. Out of the 35 rice varieties studied, only Gigante (18%), Moroberekan (19%) and NERICA-L 42 (32%), have the least yield losses and RYMV resistance characteristics. The three varieties (Gigante, Moroberekan and NERICA-L 42) are known to possess stable resistance characteristic to RYMV disease and will comparatively be suitable for cultivation in areas where RYMV incidence is endemic and on a long term be used by rice breeders as sources for breeding for durable resistance to RYMV disease in Nigeria